2018
DOI: 10.5505/vtd.2018.70894
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery Outcomes: Comparison of 2.4 mm and 2.8 mm Clear Corneal Incisions

Abstract: Objective: To compare clinical outcomes of cataract surgeries with 2.4 mm and 2.8 mm clear corneal incisions. Materials and Methods: This retrospective study comprised 2 groups of cataract surgery cases with different wound lenghts of group 1; 2.4 mm and group 2; 2.8 mm. We evaluated 80 eyes of 72 patients with 3-month follow-ups. Procedures carried out using the temporal self-sealing incision technique. Measured intraoperative parameters included phacoemulsification time, mean cumulative dissipated ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this study, OCCI were utilised to reduce up to 1.0D of corneal astigmatism in the OTS group. Kavşut et al 9 , reported a mean SIA of 0.26D using a 2.40mm keratome, and 0.40D with a 2.8mm keratome. Ernest et al 10 documented a mean SIA from a 2.20mm keratome of 0.25D and Can et al reported an SIA with a 2.80mm keratome of 0.46D 20 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this study, OCCI were utilised to reduce up to 1.0D of corneal astigmatism in the OTS group. Kavşut et al 9 , reported a mean SIA of 0.26D using a 2.40mm keratome, and 0.40D with a 2.8mm keratome. Ernest et al 10 documented a mean SIA from a 2.20mm keratome of 0.25D and Can et al reported an SIA with a 2.80mm keratome of 0.46D 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Paired OCCI on the steep axis have been shown to reduce corneal astigmatism during CS [9][10][18][19][20][21] . In this study, OCCI were utilised to reduce up to 1.0D of corneal astigmatism in the OTS group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations